(untitled) (World Bulletin of Public Health, 2025)
In the structure of general ENT pathology, diseases affecting the nose and paranasal sinuses come first, followed by diseases affecting the ears. At the same time, most ear diseases are associated with the development of various types of hearing loss not only in the acute phase of the disease, but also often acquire a chronic character. According to epidemiological data, more than half of people suffering from hearing loss are of working age, which determines the extreme importance of effective therapies for these diseases from both a social and economic point of view.